Long lasting training effects: the comparison of two strength training programs - Pinque, T. E. (1993)
Abstract: This study was designed to: a) compare strength gains obtained from the Multi Set Percentage Program to the strength gains of the Descending Half Pyramid Program over an eight week training period; b) compare strength levels retained by each subject from both programs after a two week break of no weight training to determine if either program was conducive to the retention of strength gains previously acquired. Women varsity athletes at Duke University volunteered to serve as subjects for the study, (N=13). Both strength training programs brought about significant increases in strength (p=.05); however, neither program was superior to the other. Subjects in both programs showed no significant loss in strength following the two week period of no weight training. There was an overall decrease in body fat percentage for all subjects; although not significant between programs. (Pinque, T.E. Long lasting training effects: the comparison of two strength training programs, 1993. M.A., University of North Carolina at Chapel Hill. (106pp 2f $10.00) PH 1471)